Agricultural land use conflict identification and land degradation risk analysis from the perspective of spatial matching in the Ili River Valley - DONG Guanglong, WANG Jue, WANG Han, CHENG Weiya, LIU Zheng, ZHANG Wenxin (Ziyuan Kexue)
[Objective] This study aimed to accurately identify agricultural land use conflicts and related potential land degradation risks, and provide a scientific reference for the rational allocation of land resources, optimization of agricultural production spatial layout, and protection of healthy and sustainable agricultural development and national food security. [Methods] In this study, a diagnosis and recognition method for agricultural land use conflicts was constructed from the perspective of spatial matching, and the types, intensity, and spatial distribution patterns of agricultural land use conflicts were quantitatively described. Combined with the evaluation results of soil erosion sensitivity, land degradation risk areas were identified based on spatial combination matrix. [Results] (1) Compared with the oversimplified land capacity evaluation method, the agricultural suitability evaluation method was more suitable for the characterization of natural land use in the Ili River Valley; (2) In 2020, the area of agricultural land use conflict zone in the Ili River Valley was 20142.59 km2, accounting for 29.30% of the total study area. The actual land use in this region exceeded the appropriate range of natural land use determined by natural resource endowments, and the spatial mismatch of agricultural resources was obvious. (3) The soil erosion insensitive area in the Ili River Valley was the most widely distributed, covering an area of 44442.46 km2, accounting for 67.14% of the total study area, and widely distributed in the flat and open plain area of the Ili River Valley. The moderately sensitive, highly sensitive, and extremely sensitive areas were 3811.25, 3692.74, and 2683.44 km2, respectively, which are mainly distributed in the northern part of Khorgos City, the southern part of Zhaosu County, and the northern part of Nilek County. (4) The high land degradation risk area covered 4200.92 km2, accounting for 20.95% of the agricultural land use conflict area and 7.63% of the Ili River Valley, mainly distributed in the north, middle, and south Tianshan Mountains with rugged terrain and harsh natural environment making it suitable for woodland or mixed forest and grass. However, it’s current used as artificial pasture coupled with overgrazing has increased the risk of land degradation. [Conclusion] Agricultural land use conflict in the Ili River Valley is not serious, and there are scattered high degradation risk areas. It is necessary to formulate measures for the sustainable use of land resources in view of potential land degradation risks, solve the problems of agricultural spatial mismatch and conflict, coordinate the relationship between food production, livestock development, and ecological protection, and optimize the spatial distribution of agricultural production.